Proses Komunikasi Dalam Rawatan Pemulihan Dadah: Kajian Kes Di Pondok Remaja Inabah, Kuala Nerang, Kedah - Suria Hani A. Rahman; Mohd Faizal Kasmani; Muhammad Khairi Mahyuddin; Noor Adzrah Ramle (Universiti Sains Islam Malaysia, 2024)
The proclamation of National Drug Policy on 19 February 1983 by former Prime Minister, Y.A.B. Dato' Seri Dr. Mahathir Mohamad (presently Tun Dr. Mahathir) has proven that the Government is serious in combating drug abuse. This new strategy, which endorsed by the National Drug Council on 11 June 1996, were focusing more on the prevention steps, enforcement and rehabilitation efforts for those involved in this substance misuse. The drafting of the policy is seen significant in shaping Malaysian as drug-free society. Apart from regular rehabilitation approach, an alternative wield of spiritual element were applied as part of a drug treatment. Based on the scenario, this study will examine the human communication approach implemented in spiritual-based treatment centre, Pondok Remaja Inabah, Kuala Nerang, Kedah. As an independent treatment hub, they exercise Islamic-based healing method during the treatment phases. Therefore, this study aims to distinguish the effectiveness of communication process from three perspectives and indicators; intrapersonal, interpersonal and group communication. Observation via questionnaire will be conducted to obtain information and feedback from the inmates. Based on variables constructed, the research findings will describe most effective communication process during the treatment and in addition to that, remarks are expected from the inmates for future betterment of Pondok Remaja Inabah.